Hidden protectionism? Evidence from non-tariff barriers to trade in the United States - Robert Grundke; Christoph Moser (University of Salzburg, Department of Social Sciences and Economics, 2016)
Can the enforcement of product standards be protectionism in disguise? This paper estimates the costs of non-compliance with U.S. product standards, using a new database on U.S. import refusals from 2002 to 2014. We find that import refusals decrease exports to the United States. This trade reducing effect is driven by developing countries and by refusals without any product sample analysis, in particular during the Subprime Crisis and its aftermath. We also provide evidence that given product standards have been enforced more strictly during the crisis. These results are consistent with the existence of counter-cyclical, hidden protectionism due to non-tariff barriers to trade in the United States.
Keywords: F13; F14; O24; F63; 330; hidden protectionism; international trade; developing countries; import refusals; regulatory costs; disaggregated; United States